Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Smartphone Huawei Pada Erafone Cabang Jombang Sudimara Di Kota Tangerang Selatan - Muhammad Zakaria; Purwanti Purwanti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study is to determine the effect of price and product quality on purchasing decisions for Huawei smartphones at Erafone Jombang Sudimara Branch in South Tangerang City partially and simultaneously. The research method used is quantitative. In this study, the consumers of Erafone Jombang Sudimara Branch in South Tangerang City were 932 people and the sample determination used probability sampling with the 10% slovin formula, so a sample of 90 respondents was obtained. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. The results of the calculation of the t-test value were 7.640 and a significance of 0.000 <0.05. then Ha was accepted and H0 was rejected, it can be stated that price (X1) has a significant effect on purchasing decisions (Y). The results of the calculation of the t-test value were 8.985 and a significance of 0.000 <0.05. then Ha was accepted and H0 was rejected, it can be stated that product quality (X2) has a significant effect on purchasing decisions (Y). Multiple linear regression analysis Y = 13,865 + 0.373 X1 + 0.373 X2, Based on the results of the study, it was found that the correlation value of the price variable (X1) and product quality (X2) was 0.772, meaning it had a strong level of relationship. Based on the R Square value of 0.772, this shows that 100% - 77.2%. the remainder is 22.8%. Based on the results of the analysis, namely the ANOVA test, the F count value was 64,089 while the F table (0.05) for n = 87 was 2.71. So F count> from F table (0.05) or 64,089> 2.71, with a significant level of 0.000 because 0.000 <0.05, it can be said that price (X1), product quality (X2) positively and significantly influence purchasing decisions (Y)..